DEVELOPMENT OF AN EMPOWERMENT MODEL FOR PAKET C LEARNERS ORIENTED TOWARD INDEPENDENCE AND ENTREPRENEURIAL SKILLS - Tiffany Estherlita; Ansori Ansori; Heris Hendriana (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aimed to develop an empowerment model for Paket C learners oriented toward independence and entrepreneurial skills. Problems in equivalency education indicated that learning processes remained instructional and had not fully supported learners’ independence and potential development. This research employed a Research and Development (R&D) approach focusing on conceptual model development and expert validation. The research stages included needs analysis, theoretical review, model design, development of syntax and indicators, and validation by community education experts and PKBM practitioners. The results produced the ICRIP Empowerment Model (Innovative, Creative, Responsive, Independent, Potential Development), which consisted of philosophical, theoretical, and conceptual foundations, operational principles, empowerment syntax, working mechanisms, and measurable empowerment indicators. The model was conceptually feasible and demonstrated strong potential to be applied as a sustainable empowerment approach in Paket C equivalency education.